2017
DOI: 10.1371/journal.pone.0189756
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genistein on the gut microbiome of humanized mice and its role in breast tumor inhibition

Abstract: Since dietary polyphenols can have beneficial effects in prevention and treatment of cancer, we tested the hypothesis that breast cancer patients’ intestinal microbiota is modulated by genistein (GE), an isoflavone found in soy, and that microbial alterations may offset the side effects brought about by chemotherapy. We demonstrated successful humanization of germ-free mice by transplanting fecal samples from breast cancer patients before and after chemotherapy. Mice were then grouped based on chemotherapy sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 53 publications
1
57
0
Order By: Relevance
“…It has also been shown that genistein increases the formation of metabolites derived from the benzoate metabolism. In fact, there is evidence that genistein can be biotransformed by the gut microbiota to 4-ethylphenol 44. In particular, 4-ethylphenylsulfate, a product derived from 4-ethylphenol, is associated with the maximal aerobic capacity in healthy subjects, as well as prediction of lean body mass 24 45.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that genistein increases the formation of metabolites derived from the benzoate metabolism. In fact, there is evidence that genistein can be biotransformed by the gut microbiota to 4-ethylphenol 44. In particular, 4-ethylphenylsulfate, a product derived from 4-ethylphenol, is associated with the maximal aerobic capacity in healthy subjects, as well as prediction of lean body mass 24 45.…”
Section: Discussionmentioning
confidence: 99%
“…The soy flavonoids increased with the test food(s) in this study, including daidzein, genistein, and glycitein, have been associated with a number of positive health attributes, including antioxidant, anticancer, and anti-inflammatory properties [ 39 , 40 , 41 ]. There is also some evidence that genistein can modulate the gut microbiome to reduce tumor growth [ 42 ]. In addition, consumption of soy protein has been shown to slow the decline of estimated GFR and decrease proteinuria in patients with CKD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of soy or exposure to phytoestrogens alters the gut microbiota denizens (14)(15)(16)(17)(18)(19)(20)(21)(22). Most current studies have focused on whether direct or adult exposure affects the gut microbiome, although there is every reason to believe that developmental exposure to such chemicals influences infant gut bacteria populations, which may be even more vulnerable during this initial colonization period than those of adults.…”
Section: Effects Of Phytoestrogens On the Gut Microbiomementioning
confidence: 99%
“…A similar study found that ingestion of daidzein positively correlated with greater abundance of Asaccharobacter celatus and Slackia isoflavoniconvertens, two equol producing bacteria (13). Other rodent and human studies suggest that genistein (GEN) or soy based foods impacts gut microorganisms (14)(15)(16)(17)(18)(19)(20)(21)(22). Alterations in bacteria residing in the gut or skewing to pathobionts (otherwise considered gut dysbiosis) may result in neurobehavioral changes, giving rise to the term the microbiomegut-brain axis (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%